Directional diffusion of carbon atoms and lattice distortion in the high-speed changing dynamic temperature field – A novel method to manufacture high tribological performance cermets. (December 2022) - Liu, Junbo; You, Qianbing; Huo, Yunliang; Xiong, Ji; Guo, Zhixing; Yang, Lu; Zhang, Hong; Zhao, Jianfeng; Wang, Longgang
Abstract: The research was aiming at exploring a novel approach to manufacture high tribological performance cermets by treating in a high-speed changing dynamic temperature field. Results showed that with the method, carbon atoms migrated from the subsurface region to the surface region. Atoms escaped from the crystals and large-angle boundaries (>10°) and dislocation were formed. During ball-on-disk wear tests at 800 °C, fine furrows with a smallest depth of 8 μm was obtained on the cermets after treated for 30 cycles, which showed highest Vicker hardness of 1810 HV30 and best toughness of 9.7 MPa.m 1/2 due to the strengthening effect of large angle boundaries and dislocations. The cermets after treated for 100 cycles displayed the lowest COF of 0.17 due to graphite phase formed by carbon atoms migration. Graphical abstract: Unlabelled Image Highlights: High performance cermets were fabricated by treated in the high-speed changing dynamic temperature field. After treated for 30 cycles, cermets showed the highest hardness (1810 HV30 ), best toughness (9.7 MPa.m 1/2 ) and best resistance to deformation and wear due to the strengthening effect of large angle boundaries and dislocations. After treated for 100 cycles, graphite appeared, cermets showed good lubricating properties.